Novel Reclassification of Adult Diabetes Is Useful to Distinguish Stages of β-Cell Function Linked to the Risk of Vascular Complications: The DOLCE Study From Northern Ukraine - Fedotkina, Olena; Sulaieva, Oksana; Ozgumus, Turkuler; Cherviakova, Liubov; Khalimon, Nadiya; Svietleisha, Tetiana; Buldenko, Tetiana; Ahlqvist, Emma; Asplund, Olof; Groop, Leif; Nilsson, Peter M.; Lyssenko, Valeriya (Frontiers in Genetics, 2021)
Background. Presently, persons with diabetes are classified as having type 1 (T1D) or type 2 diabetes (T2D) based on clinical diagnosis. However, adult patients exhibit diverse clinical representations and this makes treatment approaches challenging to personalize. A recent Scandinavian study proposed a novel classification of adult diabetes into five clusters based on disease pathophysiology and risk of vascular complications. The current study aimed to characterize new subgroups of adult diabetes using this strategy in defined population from northern Ukraine. Methods. We analyzed 2,140 patients with established diabetes from the DOLCE study (n=887 with new-onset diabetes and n=1,253 with long duration). We used the k-means approach to perform clustering analyses using BMI, age at onset of diabetes, HbA1c, insulin secretion (HOMA2-B), and insulin resistance (HOMA2-IR) indices and glutamic acid decarboxylase antibodies (GADA) levels. Risks of macro- (myocardial infarction or stroke) and microvascular (retinopathy, chronic kidney disease, and neuropathy) complications and associations of genetic variants with specific clusters were studied using logistic regression adjusted for age, sex, and diabetes duration. Results. Severe autoimmune diabetes (SAID, 11% and 6%) and severe insulin-deficient diabetes (SIDD, 25% and 14%) clusters were twice as prevalent in patients with long-term as compared to those with new-onset diabetes. Patients with long duration in both SAID and SIDD clusters had highest risks of retinopathy, and elevated risks of CKD. Long-term insulin-resistant obese diabetes 1 (IROD1) subgroup had elevated risks of CKD, while insulin-resistant obese diabetes 2 (IROD2) cluster exhibited the highest HOMA2-B, lowest HbA1c, and lower prevalence of all microvascular complications as compared to all other clusters. Genetic analyses of IROD2 subgroup identified reduced frequency of risk alleles in the TCF7L2 gene as compared to all other clusters, cumulatively and individually (p=0.0001). Conclusion. The novel reclassification algorithm of patients with adult diabetes was reproducible in this population from northern Ukraine. It may be beneficial for the patients in the SIDD subgroup to initiate earlier insulin treatment or other anti-diabetic modalities to preserve β-cell function. Long-term diabetes cases with preserved β-cell function and lower risk for microvascular complications represent an interesting subgroup of patients for further investigations of protective mechanisms.